A comparative study on biological properties and chemical profiles of different solvent extracts from Centaurea bingoelensis, an endemic plant of Turkey. (March 2021) - Uysal, Ahmet; Zengin, Gokhan; Mahomoodally, Mohamad Fawzi; Picot-Allain, Carene; Jekő, József; Cziáky, Zoltán; Rodrigues, Maria João; Ak, Gunes; Polat, Rıdvan; Urusan, Zeynep; Sinan, Kouadio Ibrahime; Custodio, Luisa
Graphical abstract: Highlights: Chemical profile and biological properties of Centaurea bingoelensis extracts were investigated. Sixty-seven and sixty-two compounds were detected in methanol and water extracts, respectively. Hydro-methanol extract exhibited the best activity in DPPH (70.72 mg/TE) and ABTS (76.53 mg TE/g) assays. The methanol extract was most toxic against HepG2 cells. C. bingoelensis is a promising candidate for the development of phytopharmaceuticals. Abstract: This study focused on the biological evaluation and chemical characterization of Centaurea bingoelensis, an endemic plant to Turkey. Different solvent extracts (hexane, dichloromethane (DCM), ethyl acetate (EA), methanol, hydro-methanol, and water extracts) were prepared. The antioxidant, enzyme inhibitory, antimicrobial and cytotoxic activities were investigated. The hydro-methanol extract, possessing high phenolic content (41.57 mg gallic acid equivalent (GAE)/g extract), showed highest reducing capacity (136.87 and 82.16 mg Trolox equivalent[TE]/g extract, for cupric reducing antioxidant capacity and ferric reducing antioxidant power, respectively) and radical scavenging potential (70.72 and 76.53 mg TE/g extract, against 2, 2-diphenyl-1-picrylhydrazyl and 2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), respectively). Ultra performance liquid chromatography - tandem mass spectrometer (UHPLC/MS/MS) analysis revealed the presence of 67 and 62 compounds in the methanolic and water extracts, respectively. According to the broth microdilution results, DCM and EA extracts showed significant antimicrobial activity with Sarcina lutea being the most sensitive bacterium to the extracts (MIC = 0.19 (DCM) and 0.097 mg/mL (EA)). Most extracts showed promising antifungal activity against Candida albicans . The methanol extract was most toxic against human hepatocarcinoma (HepG2) cells, and also significantly reduced the cell viability of the non-tumoral murine bone marrow stromal (S17) cells. This study has provided valuable scientific data on this endemic plant which can be considered as a promising candidate for the development of novel phyto-pharmaceuticals.